Development of Competencies in the Field "Physical Development and the Formation of a Healthy Lifestyle" Among Preschoolers in the Process of Physical Education - Sharipova, D.; Tairova, M. (International Journal on Integrated Education, 2023)
The article deals with the development of competencies in the field "Physical development and the formation of a healthy lifestyle" among preschoolers in the process of physical education.